Diversifying Chile's climate action away from industrial plantations. Issue 124 (October 2021) - Hoyos-Santillan, Jorge; Miranda, Alejandro; Lara, Antonio; Sepulveda-Jauregui, Armando; Zamorano-Elgueta, Carlos; Gómez-González, Susana; Vásquez-Lavín, Felipe; Garreaud, Rene D.; Rojas, Maisa
Highlights: Climate change threatens the carbon sink capacity of forests in Chile. Industrial plantations do not contribute towards achieving carbon neutrality. Wildfire emissions exceed the nationally determined contributions mitigation. Climate actions should diversify including a wider range of nature based solutions. Conservation and restauration of wetlands can contribute to carbon neutrality. Abstract: As president of the Climate Change Conference of the Parties, Chile has advocated for developing ambitious commitments to mitigate greenhouse gas emissions to achieve carbon-neutrality by 2050. However, Chile's motivations and ambitious push to reach carbon-neutrality are complicated by a backdrop of severe drought, climate change impacts ( i.e ., wildfires, tree mortality), and the use of industrial plantations as a mitigation strategy. This has become more evident as widespread and severe wildfires have impacted large areas of industrial plantations, transforming the land-use, land-use change, and forestry sector from a carbon sink to a net carbon source. Consequently, Chile must diversify its climate actions to achieve carbon-neutrality. Nature-based solutions, including wetlands-peatlands and oceans, represent alternative climate actions that can be implemented to tackle greenhouse gas emissions at a national level. Diversification, however, must guarantee Chile's long-term carbon sequestration capacity without compromising the ecological functionality of biodiverse tree-less habitats and native forest ecosystems.